Estimation of the effect of redox treatment on microstructure and tendency to brittle fracture of anode materials of YSZ–NiO(Ni) system - Vasyliv, Bogdan; Kulyk, Volodymyr; Duriagina, Zoia; Mierzwinski, Dariusz; Kovbasiuk, Taras; Tepla, Tetiana (Eastern-European Journal of Enterprise Technologies, 2020)
The effect of reduction treatment in a high-temperature (600 °C) hydrogen-containing environment on the microstructure and tendency to brittle fracture of YSZ–NiO(Ni) materials for solid oxide fuel cell anodes has been studied. To assess the crack growth resistance of the ceramics, the Vickers indentation technique was adapted, which allowed estimating the microhardness and fracture toughness of the material in the complex. The requirements for high porosity of the anodes to ensure functional properties show that the strength may be an insufficient characteristic of the bearing capacity of the anode. More structurally sensitive characteristics are needed to assess its crack growth resistance. The average levels of microhardness of YSZ–NiO ceramics in the as-sintered state and YSZ–NiO(Ni) cermets (2.0 GPa and 0.8 GPa, respectively) and their fracture toughness (3.75 MPa·m1/2 and 2.9 MPa·m1/2, respectively) were experimentally determined. It was found that the microstructure of YSZ–NiO(Ni) cermet after redox treatment is formed by a YSZ ceramic skeleton with refined Ni-phase grains combined in a network, which provides increased electrical conductivity. Along with higher porosity of the cermet, its fracture toughness is not lower than that of the one-time reduced cermet due to the implementation of the bridging toughening mechanism of fracture. The proposed treatment method allowed forming the microstructure of the anode material, resistant to crack propagation under mechanical load. The propensity of the anode material to brittle fracture on the basis of evaluation of its crack growth resistance and analysis of the microstructure and fracture micromechanism was substantiated. This result is interesting from a theoretical point of view. From a practical point of view, the developed technique allows determining the conditions of redox treatment in the technology of manufacturing fuel cell anodes